Determining energy-efficient operation modes of the propulsion electrical motor of an autonomous swimming apparatus - Volyanskaya, Yana; Volyanskiy, Sergey; Volkov, Aleksandr; Onishchenko, Oleg (Eastern-European Journal of Enterprise Technologies, 2017)
Ensuring the maximum possible navigation range and duration of autonomous functioning of an unmanned swimming apparatus for special purposes was solved by minimizing energy consumption of the electromotive system. In order to achieve it, we proposed a procedure for the estimation of power losses at different static loads and power voltage of the asynchronous baro-unloaded motor of an autonomous swimming device. Special features of the procedure include determining an essentially descending character, loading characteristics of a baro-unloaded asynchronous motor of low capacity; determining the values for magnetic flux of the induction motor, at which under steady operational modes and a partial load, the total power losses are minimal; establishing dependences of performance efficiency and the stator current when controlling voltage at different loads. Employing the proposed procedure in the control algorithm over electromotive system of the device made it possible to enable an energy-efficient change in power voltage at a constant frequency and partial loads